2020
DOI: 10.1016/j.clinbiomech.2020.105232
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying varus thrust in knee osteoarthritis using wearable inertial sensors: A proof of concept

Abstract: Background: Varus thrust during walking, visualized as excessive frontal plane knee motion during weight acceptance, is a modifiable risk factor for progression of knee osteoarthritis. However, visual assessment does not capture thrust severity and quantification with optical motion capture is often not feasible. Inertial sensors may provide a convenient alternative to optical motion capture. This proof-ofconcept study sought to compare wearable inertial sensors to optical motion capture for the quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…By analysing those data, the potential OA-related changes could be recognized. Besides, the quantification of varus thrust in patients with medial knee OA could be done with the placement of inertial sensor at mid-thigh [17].…”
Section: Introductionmentioning
confidence: 99%
“…By analysing those data, the potential OA-related changes could be recognized. Besides, the quantification of varus thrust in patients with medial knee OA could be done with the placement of inertial sensor at mid-thigh [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies used different subsets of a full IMU sensor setup to demonstrate the presence of joint kinematic differences in knee OA and hip OA 70e74 . Besides overall joint kinematics, specific kinematic targets like trunk lean/center of mass position 68 or knee varus thrust 75 can be feasibly tracked with IMUs, making IMUs useful for targeted biomechanics studies in OA.…”
Section: Wearablesmentioning
confidence: 99%
“…Single-leg sensor metrics were associated with surrogate measures of varus thrust, and midthigh adduction velocity was significantly associated with peak external knee adduction moment 3 IMU b (Trigno IM Sensors, Delsys Inc) on thigh, midshank, and distal shank Knee OA a (n=26) Costello et al, 2020 [33] Positive correlation between lateral thrust and change in medial meniscus extrusion 2 IMU c (WAA-010, ATR-Promotions) placed on tibia and foot Knee OA (n=44) Ishii et al, 2020 [34] Moderate correlation found between acceleration peak in IMU frame and KAM, values from shank IMU had strongest correlation 6 IMU c (TSND151, ATR-Promotions) on pelvis, sternum, shanks, and thighs Knee OA (n=22) Iwama et al, 2021 [35] High accuracy and repeatability of foot progression angle measures, and feedback effectiveness was similar between wearable and laboratory feedback setups 7 IMU b (MTw, Xsens Technologies BV) on pelvis, thighs, shanks, and feet Healthy (n=11) Karatsidis et al, 2018 [38] Two machine learning algorithms were highly accurate (R 2 approximately 0.95) in predicting KAM using IMU input 2 IMU c (DA14583, Dialog Semiconductor) on malleoli Healthy (n=12), knee OA (n=78) Wang et al, 2020 [36] Good correlation coefficients to discriminate between different foot progression angle walking conditions 2 IMU b (MTw Awinda, Xsens Technologies BV) on feet Healthy (n=5) Wouda et al, 2021 [37] Participants were able to respond to feedback during walking and adopt target foot progression angle conditions Single IMU b (custom-made) embedded in shoe sole Healthy (n=10) Xia et al, 2020 [39] a OA: osteoarthritis.…”
Section: Findings Sensor Population Studymentioning
confidence: 99%
“…Different sensor configurations during walking have been used to quantify varus thrust in gait; and one study using sensors on the thigh, midshank, and distal shank showed that midthigh sensor metrics were associated with optical motion capture thrust measurements while having less variability than midshank sensors [33]. Another study using sensors on the tibial tubercles and dorsal surface of the foot found greater peak varus thrust in the severe OA group when compared with their early-stage OA group [34].…”
Section: Findings Sensor Population Studymentioning
confidence: 99%